High-Performance Non-enzymatic Glucose Sensors Based on CoNiCu Alloy Nanotubes Arrays Prepared by Electrodeposition - Gong, Xuewen; Gu, Yan; Zhang, Faqiang; Liu, Zhifu; Li, Yongxiang; Chen, Guanyu; Wang, Bo (Frontiers in Materials, 2019)
Transition metal alloys are good candidate electrodes for non-enzymatic glucose sensors due to their low cost and high performance. In this work, we reported the controllable electrodeposition of CoNiCu alloy nanotubes electrodes using AAO as template. Uniform CoNiCu alloy arrays of nanotubes about 2 μm in length and 280 nm in diameter were obtained by optimizing the electrodeposition parameters. SEM and EDS measurements indicated that the as-prepared alloy nanotubes arrays are composed of 64.7 wt% Co-19.4 wt% Ni-15.9 wt% Cu. Non-enzymatic glucose sensing measurements indicated that the CoNiCu nanotubes arrays possessed a low detection limit of 0.5 μM, a high sensitivity of 791 μA mM-1 cm-2 from 50 to 1551 μM and 322 μA mM-1 cm-2 from 1551 to 4050 μM. Besides, they showed high reliability with the capacity of anti-jamming. Tafel plots showed that alloying brought higher exchange current density and faster reaction speed. The high performance should be due to the synergistic effect of Co, Ni and Cu metal elements and high surface area of nanotubes arrays.